ISLAM DAN RESOLUSI KONFLIK INTERNASIONAL - Wicaksono, Arief (JPP (Jurnal Politik Profetik), 2015)
Current conflicts frequently occur in military, environmental, economic, social and political fields. Conflict in the military field usually involves not only the competitive capability of military forces and armaments, and competitive military business, but also in their efforts to strengthen their regional power or hegemony. Islam safeguards both human beings and nature in order not to compete and clash in interests. Conflict essentially stems from injustice and greed of some people. Islam has addressed such issues by ensuring the fairness and warning on human greed. Islamic shariah basically aims to keep the balance in religion, soul and human life, wealth, honor and environment. Islamic shariah is not man-made, which overlooks the potentials of human beings and nature. Yet, it is the guidance of the Creator of both human beings and nature, which the former is well acquainted with all their issues, needs and harmony of human beings and His creation.